Frequency of afmatic attack and its behavioral factors among asthmatic patients in Hospital Sungai Buloh, 1995 - Saiah Abdullah,; Khalib Abdul Latip, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Repetitive asthmatic attacks poised a crucial problem on asthmatic patients as well as their families, school, place of work, hospitals and the general public. A cross sectional study is therefore carried out with regard to the frequency of asthmatic attacks in relation to the behavioral factor on a number of asthmatic patients who attended the Sungai Buloh Hospital on December 1995. One hundred and ten respondents were universally selected. This research are catried out in the form of interview with the aid of questionnaires and in observing the correct techniques in using the Metered Dose inhaler (MDI). As a result, the study indicates 50.0% of the respondent was suffering from severe asthmatic attacks. Thirty-six decimal eight percent (36.8%) of the respondent shows negative practices. The more serious one is in not taking the medication as prescribed which consist of 69.1% of the respondents. Only 66.9 % of the respondents bears a complete knowledge of Asthma. Seventy two percent (72 % ) shows positive attitude and 34.5 % have false belief about asthma. The results shows significant different between the patients with mild attacks and those with serious attacks in relations to the knowledge about the signs and symptoms of asthma as in I patophysiology ( p< 0.05 ). Out of 69.1 % of the respondents who uses the MDI only r .37 % of them shows correct usage. The techniques in MDI usage shows a significant d' difference with regard to the knowledge about inhaler ( p< 0.01 ). There is assocciations between those who uses the MDI with those who do not by the number of asthmatic attacks experiences. In conclusion, the knowledge of every respondent should be , improved inorder that they will contribute to themselves in the control of asthmatic , attacks. By. doing so. Who provide considerable assistance for the patients to upgrade the level of their well being m health and productivity .